Spatial and temporal clustering analysis on chlorophyll-a data distribution - Fitrianah, Devi (International Journal of Engineering and Technology, 2018)
The motivation of this study is to serve as an alternative approach to most chlorophyll analysis studies that utilize overlay analysis with chlorophyll-a imaging. Mostly, the chlorophyll overlay analysis take many steps in processes, not to mention the bigger the observation duration for the data, the longer it takes to process. In this study, a spatial and temporal clustering analysis was conducted to obtain areas that have abundant chlorophyll-a. The spatial distribution was determined using the DBSCAN algorithm, while the temporal distribution was deter-mined via the fuzzy c-means algorithm. From this study, we can obtain information on the distribution of chlorophyll-a clearly based on the location and the time through a given visualization in advanced. There is no need to do overlaying chlorophyll-a imaging one by one. The results of the spatial and temporal clustering provide an easy-to-read visualization regarding information on the chlorophyll-a distribution based on location and time.Â Â